Big Red: A Development Environment for Bigraphs - Faithfull, Alexander; Perrone, Gian; Hildebrandt, Thomas (Electronic Communications of the EASST, 2013)
We present Big Red, a visual editor for bigraphs and bigraphical reactive systems, based upon Eclipse. The editor integrates with several existing bigraph tools to permit simulation and reachability analysis of bigraphical models. We give a brief introduction to the bigraphs formalism, and show how these concepts manifest within the tool using a small motivating example developed in Big Red. We go on to outline its architecture and implementation, and comment on possible future work.